BIO-ACTIVITIES AND PHYTOCHEMICAL INVESTIGATION OF CNESTIS PALALA (LOUR.) MERR. - Dej-adisai, Sukanya; Tinpun, Kittiya; Wattanapiromsakul, Chatchai; Keawpradub, Niwat (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: In traditional medicines, the root of Cnestis palala was used for the treatment of stomach ache, malaria, urinary track disorders and snakebite. The seed was used for poisoning rat and stray dogs. However, the bioactivities and chemical constituents have not been reported. So, this will be the first report. Material and Methods: Biological investigations of C. palala extracts against bacteria (Staphylococcus aureus, Staphylococcus epidermidis, Propionibacterium acnes, Escherichia coli, and Pseudomonas aeruginosa), fungi (Trichophyton mentagrophytes, Trichophyton rubrum and Microsporum gypseum), yeast (Candida albicans), tuberculosis (Mycobacterium tuberculosis), malaria (Plasmodium falciparum) and cancer cell lines (MCF-7 and HT-29) were evaluated. The chromatographic and spectroscopic techniques were used for the isolation and identification of pure compounds. Results: The results showed that the ethanol leaf and bark extracts were active against S. aureus and S. epidermidis. The hexane leaf and seed extracts and petroleum ether bark and root extracts showed strongly inhibition values against MCF-7. Moreover, the petroleum ether bark extract exhibited high inhibition value against HT-29. Seven compounds were isolated as β-sitosterol-glucoside (CP1), hydroquinone (CP2), β-sitosterol (CP3), mixture of fatty acids (CP4) and ethyl caffeate (CP5), scopoletin (CP6) and 2-nonenal (CP7). The CP2 was strongly active against S. aureus and S. epidermidis, the MIC was showed 30.10 µg/ml and 15.05 µg/ml and the MBC was showed 15 µg/ml and 7.5 µg/ml, respectively. Conclusion: These results suggested that C. palala is a great potential source of anti-microbial agents. Hence, this is the first study, which will be the database for chemical constituents and bioactivities of C. palala.